THE IMPLEMENTATION OF PARTNER READING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Makbul, Makbul; Anggreni, Afrillia; Munir, Syahrul; Mukrim, Mukrim (Tadulako University, 2025)
The objective of this research is to find out whether or not the implementation of partner reading strategy improve reading comprehension of the eight grade students of SMP Negeri 1 Tomini. This study limits on the use of Partner Reading strategy in improving students’ reading comprehension which focuses on literal meaning and the narrative text. The researcher used a quantitative method and a pre- experimental as the research design. The population of this research was eight- grade students consisting of 143 students. The researcher used random sampling and took VIII B as the sample in this study. The instrument of this study was test consisted essay and true or false. The result of the pre-test was 41,23 while post- test was 75.56. By applying 0.05 level of significance, the researcher found that the value of the t-counted is higher than t-table (17.51 > 1.706) This means that the hypothesis is accepted. In other words, the implementation of partner reading strategy improve students reading comprehension of the eight grade of SMP Negeri 1 Tomini.